5-Methoxytryptophan Sensitizing Head and Neck Squamous Carcinoma Cell to Cisplatitn Through Inhibiting Signal Transducer and Activator of Transcription 3 (STAT3) - Su, Yu-Chieh; Wang, Chih-Chun; Weng, Jui-Hsi; Yeh, Shyh-An; Chen, Po-Jen; Hwang, Tzer-Zen; Chen, Huang-Chi (Frontiers in Oncology, 2022)
Head and neck squamous cell carcinoma (HNSCC) is a common cancer of the oral cavity. Cisplatin (CDDP) is the ideal chemo-radiotherapy used for several tumor types, but resistance to the drug has become a major obstacle in treating patients with HNSCC. 5-methoxytryptophan (5-MTP), a 5-methoxyindole metabolite of tryptophan metabolism, reduces inflammation-mediated proliferation and metastasis. This study aimed to assess the anti-oral cancer activity of 5-MTP when used alone or in combination with CDDP. Results showed that CDDP dose dependently reduced the growth of SSC25 cells but not 5-MTP. The combination of CDDP and 5-MTP exerted additional inhibitory effect on the growth of SSC25 cells by attenuating the phosphorylation of STAT3. In the 4-nitroquinoline-1-oxide-induced oral cancer mouse model, 5-MTP sensitized the reduction effect of CDDP on tumorigenesis, which restricted the tongue tissue in hyperkeratotic lesion rather than squamous cell carcinoma. The combination of CDDP and 5-MTP may be a potent therapeutic strategy for HNSCC patients with radiotherapy.